Functional outcome and quality of life after meningioma surgery: a systematic review. (19th January 2021) - Corniola, Marco V.; Meling, Torstein R.
Abstract: Assessment of long‐term functional outcomes after meningioma surgery is important. We systematically reviewed the literature on health‐related quality of life (HrQoL) and functional disability (FD) of patients after surgery for intracranial meningiomas. Using PRISMA 2015 guidelines, we screened 289 abstracts and 43 titles were retained for full‐paper screening. 15 articles did not present enough data to meet the inclusion criteria and 7 articles failed to assess functional assessment and HrQoL. Twenty‐two articles were included in our review. HrQol was assessed in N = 18 publications, most frequently using SF‐36 ( N = 10), followed by EQ5D‐5L ( N = 4), EORTC‐QLQ ( N = 4), and the FACT questionnaire ( N = 2). The assessment of FD was reported in N = 11 publications, mostly using the KPS ( N = 8). The Barthel index was used in N = 2 publications. Follow‐up was reported in N = 12 publications, ranging from 6 months to 9 years. Scientific publications assessing long‐term postoperative HrQol and FD in patients undergoing meningioma surgery are scarce and the data are heterogeneously reported, using various scales and follow‐up protocols. Efforts should be undertaken to uniformly assess long‐term post‐operative functional outcomes in meningioma patients.